pH and Acid Base - Gary Onady; Nicholas Reo; Lawrance Prochaska (Association of American Medical Colleges, 2011)
Abstract This module integrates pH and acid-base concepts from basic lectures and readings with clinical information to enhance definitive patient care clinical decision making through team-based learning (TBL). The Henderson-Hasselbalch equation is used to apply the logarithmic pH function of hydrogen ion [H+] for calculating acid and base effects on proteins as a major theme behind this module. This task is accomplished by working through a problem set involving a premature infant recently diagnosed with Cystic Fibrosis, and the acid-base complications encountered as a result of this patient's unique disease process. Amino acid R groups that function as weak acids or bases during enzymatic protein digestion are identified and detailed as related to described mechanisms involved in general acid-base catalysis. Relevant information is then used to discriminate therapeutic interventions from the disease concepts identified. Since introducing this module, class performance on formal written exams related to pH and acid-base has improved over previous years before this module was incorporated. The students did have some interesting methods of connecting the data points from Applications Question 5. I noted zig zag lines and curvilinear lines used by some teams during the session. It may be worthwhile to note that the data points come with error ranges, so the best fit for a line averaging these points may be considered.